CONSTRUCTION OF SEWING ITEMS - Nigora Khankeldiyeva Akramovna (American Journals Publishing, 2024)
This article delves into the intricate world of crafting sewing items, providing a detailed exploration of materials, techniques, and the creative process involved. It offers valuable insights into the construction of various sewing items, catering to beginners and seasoned crafters alike. Through literature analysis, methods, results, and discussion, this article aims to enrich readers' understanding of sewing as an art form and a fulfilling DIY endeavor.
Keywords: Sewing, Crafting, DIY, Handmade, Materials, Techniques, Construction, Creative Process